Anti-Inflammation Activity of Virgin Coconut Oil In- Vitro Against Raw Cells 264.7 - M, Amin; J, Silalahi; U, Harahap; D, Satria (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective:This study aimsto determine the anti-inflammation activity of pure coconut oil on Raw Cell 264.7 induced by LPSMethods: The anti-inflammation activity test for Virgin Coconut Oil (VCO) was carried out by testing the expression of TNF-α, IL-6, IL-1β, iNOS, and COX-2 genes on RAW 264.7 cells induced by LPS by the method Reverse Transcription-Polymerase Chain Reaction (RT-PCR).Results: The test results of iNOS, TNF-α, IL-6, IL-1β, and COX-2 gene expression from VCO on RAW 264.7 cells induced by lipopolysaccharide (LPS) decreased the value of VCO density. In iNOS expression, VCO density values ​​(0,90±0,015) showed significantly different effects with positive and negative controls p<0,05, VCO IL-1β density values ​​(2,47±0,010) showed different effects. significant with normal control, positive control and negative control p<0,05, TNF-α density value on VCO (0,91±0,010) showed significantly different effects from positive control and negative control p<0,05, then the value IL-6 density at VCO (1,23 ± 0,015) showed significantly different effects from normal and positive controls p<0,05, and COX-2 density values ​​at VCO (1,02±0,015) showed significantly different effects with normal and positive controls p<0,05.Conclusion: Based on the results of this study VCO on RAW 264.7 cells induced by LPS can inhibit the expression of TNF-α, IL-6, IL-1β, iNOS, and COX-2 genes so that VCO effectively has anti-inflammatory activity.